CO22 | Assessment of coagulation profiles in septic patients using viscoelastic coagulation monitoring and rotational thromboelastometry in an internal medicine setting (Bleeding, Thrombosis and Vascular Biology, 2025)
Background and Aims: Sepsis is a life-threatening organ dysfunction caused by a dysregulated host response to infection. It is frequently associated with coagulopathy, ranging from mild coagulation activation to overt disseminated intravascular coagulation. Standard coagulation tests provide limited information, prompting the use of complementary tools for dynamic assessment. Viscoelastic methods such as rotational thromboelastometry (ROTEM) and the novel Viscoelastic Coagulation Monitoring (VCM) allow for rapid, bedside evaluation of global hemostasis. This study aims to compare VCM and ROTEM in assessing coagulation profiles in septic patients and to evaluate the potential clinical usefulness of VCM in this setting.